Integrated SPWM and LC filter for harmonic reduction in three-phase UPS inverters - Jasmin, Dang Aina; Abdul Halim, Mazliza; Azizan, Muhammad Afiq Hazwan; Mat Leh, Nor Adni; Kamarzaman, Nur Atharah (UiTM Press, 2025)
This paper presents an approach to improving Total Harmonics Distortion (THD) in a three-phase uninterruptible power supply (UPS) inverter through the integration of a Sinusoidal Pulse Width Modulation (SPWM) control strategy and an output LC filter. Initially, a comparative analysis was conducted between conventional Pulse Width Modulation (PWM) and SPWM techniques to evaluate their impact on voltage and current THD. The findings revealed that while SPWM achieved lower THD levels than PWM, the resulting THD values still exceeded the compliance limits set by IEEE 519 standards. To address this issue, an LC filter was incorporated into the system alongside the SPWM technique. Simulation results from MATLAB R2024a Simulink demonstrated a significant reduction in current and voltage THD to 0.34% and 0.38% respectively, ensuring smooth sinusoidal waveforms within IEEE 519 standards. This study highlights the effectiveness of the integrated SPWM-LC filter approach in enhancing UPS inverter performance and reducing harmonic distortion. Moreover, it contributes to Sustainable Development Goal 9 by enhancing power quality and infrastructure resilience through innovative SPWM-LC filter integration to improve UPS inverter efficiency for sustainable industrial development.